MAHKAMAH SYARIAH DARI ABAD KE ABAD: Shariah Courts from Century to Century - Yaacob, Abdul Monir (Jurnal Syariah, 2022)
This is a brief glance at the development of the Shariah Court, originally known as the Kadi Court, throughout the Malay states. The research concentrates on the period of British colonisation and the period following the country’s independence. This study takes a qualitative approach by referencing published documents. The elements, as well as document comparisons, were thoroughly analysed. Interviews with people in positions of authority were also conducted in order to gather more data. The study focuses on numerous features of the Shariah Court, including the Sultan’s power to appoint Kadi/Judges, the status of Kadi, Court buildings, Court jurisdiction, conflict of jurisdiction, Article 121 (1A) Federal Constitution, and some Shariah Court-related concerns. There are some things that have not been investigated and recorded in the description of the given with great care, but have been examined reasonably extensively. This study would help to reorganise materials on the Shariah Court that have been scattered across several publications into a single publication for the benefit of those interested in learning more about the Shariah Court, particularly academics and researchers in the field of Islamic jurisprudence.